Latin America’s challenge: A fresh look at industrial policy - Haar, Jerry (2015)
When John Price and I wrote Can Latin America Compete? several years ago, we were unflinching in our criticism of the region for failing to undertake sweeping microeconomic and institutional changes, such as improved access to capital, investment in infrastructure, and regulatory reform. We urged the region to undertake at the minimum incremental reforms across nearly a dozen areas (including public safety, judicial reform, and education) to boost its competitiveness, less it continue to lose out to emerging markets in Asia. Doi: http://dx.doi.org/10.1016/j.jefas.2015.01.004